Adaptation of the DEMQOL-Proxy for routine use in care homes: a cross-sectional study of the reliability and validity of DEMQOL-CH - Hughes, Laura J (BMJ Open, 2019)
OBJECTIVE: To investigate the routine use of a measure of quality of life (QoL) in care homes and assess its psychometric properties when used by care staff. DESIGN: A cross-sectional two-phase study. SETTING AND PARTICIPANTS: Data were collected from care staff in seven care homes in East Sussex, England. METHOD: Phase I: The ability of care staff from two care homes to use the DEMQOL-Proxy without interviewer administration was assessed using agreement analysis between a self-administered and interviewer-administered version of the instrument. Based on these findings, DEMQOL-Proxy was adapted into a new version, DEMQOL-CH, for use as a self-administered instrument in care homes. We assessed agreement between the new DEMQOL-CH and DEMQOL-Proxy to ensure DEMQOL-CH was used correctly. Phase II: A preliminary assessment of the psychometric properties of DEMQOL-CH when used routinely was completed in a further five care homes. RESULTS: Phase I: Nineteen care staff from two care homes completed QoL measurements for residents. Systematic error was identified when staff self-completed the DEMQOL-Proxy without an interviewer. We modified the DEMOoL-Proxy to create DEMQOL-CH; this reduced the error, producing a version that could be used more accurately by care staff. Phase II: Eleven care staff from five care homes rated resident QoL routinely. DEMQOL-CH showed acceptable psychometric properties with satisfactory reliability and validity and a clear factor structure. CONCLUSIONS: The research presents positive preliminary data on the acceptability, feasibility and performance of routine QoL measurement in care homes using an adapted version of DEMQOL-Proxy, the DEMQOL-CH. Results provide evidence to support the concept that routine measurement of QoL may be possible in care homes. Research is needed to refine and test the methodology and instrument further and to explore the potential for benefits to residents, staff and care homes in larger and more representative populations.